PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK DIGITAL TEMA PERKEMBANGAN TEKNOLOGI DI KELAS III SD - ame prilla amanda (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2023)
This study aims to: (1) produce Digital Scrapbook learning media on the Theme of Technology Development for Class III SD, (2) determine the feasibility of learning media for Digital Scrapbook on the Theme of Technology Development for Class III SD. From the results of the feasibility study by material experts, media experts and teacher responses. This research is a type of research and development with reference to the ADDIE model. Furthermore, the model was adapted into 3 stages, namely: (1) Analysis, (2) Design, (3) Development. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The media expert's review sheet consists of 15 statements which are divided into 3 aspects which get an overall "Yes" rating. The material expert review sheet consists of 15 statements that are divided into 4 aspects getting an overall "Yes" assessment The teacher response review sheet consists of 15 statements divided into 4 aspects getting an overall "Yes" assessment. Overall, the results of the study of media experts, material experts and teacher responses indicate that they have undergone revisions/repairs so as to produce digital scrapbook media that are suitable for use by third grade students of SDIT Zahra Asy-Syifa. The results of this development indicate that the use of media in learning is very necessary.